HUBUNGAN KONSEP DIRI DENGAN PERILAKU ASERTIF PADA ANAK USIA 5-6 TAHUN DI TK ISLAM RAUDHATUL ULUM KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Nurul Hikmah; Daviq Chairilsyah; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study background due to the persistence of low self-concept in children. Self-concept has an important role in determining one's behavior. A good self-concept will have a positive impact on the development of children's assertive behavior. Without being supported by an assertive behavior, then the children will encounter difficulties in social environment interaction and they will also find it difficult to succeed. This study aimed to find out the relationship between self-concept and assertive behavior in children aged 5-6 years old at Raudhatul Ulum Islamic Kindergartem Sub-District Pasir Penyu Indragiri Hulu Regency. This study was quantitative study with correlation study type. Sampling technique used in this study is a sample quota with a total sample of 77 childrens. The data collection techniques were used observation sheets. The data analysis techniques were used Pearson Product Moment Correlation Coefficient. Based on the hypothesis test result obtained correlation coefficient value of rxy = 0.465, it is greater than rtable = 0.227 (0,465 > 0,227) with significance level of 0,000 < 0,05. Level relationship resides in the strong category with the resulting determinant coefficient value is of 21.7% it can be seen that the concept of self-contribution of 21.7% to assertive behavior.Key Word: Assertive Behavior, Self-Concept